2011
DOI: 10.1590/s1517-86922011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação isocinética dos músculos extensores e flexores de joelho em jogadores de futebol profissional

Abstract: INTRODUÇÃO E OBJETIVOS: Estudos que relacionam parâmetros de desempenho muscular em diferentes esportes, e, especialmente no futebol, têm sido frequentemente reportados na literatura. Entretanto, as variações metodológicas entre os diversos estudos, o tipo de dinamômetro usado em cada pesquisa e o posicionamento dos sujeitos durante as avaliações resultam na divergência dos dados coletados. Portanto, o objetivo deste estudo foi realizar uma coleta de dados que forneçam valores sobre o perfil muscular e estabel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 18 publications
(39 reference statements)
3
20
2
19
Order By: Relevance
“…In the analysis of the average PT scores of the extensor and flexor muscles at angular speed 60º/s, both limbs showed average scores higher than the average scores found in other sports such as soccer (Zakas, 2006;Fousekis et al, 2010;Eniseler et al, 2012;Daneshjoo et al, 2013), futsal (Ferreira et al, 2010), rugby (Brown et al, 2014), basketball (Schiltz et al, 2009;Carvalho et al, 2011), handball (González-Ravé et al, 2014, and volleyball (Markou & Vagenas, 2006;Shu & Zhou, 2011). However, two studies which analyzed professional soccer players showed higher average scores of flexors than the scores of the athletes of this study (Zabka et al, 2011;Daneshjoo et al, 2013). Compared to other sports at angular speed of 180°/s, a few studies have shown average scores of the extensors lower than those of this study, similarly to the studies which analyzed futsal players (Ferreira et al, 2010), and soccer (Zakas, 2006;Fousekis et al, 2010;Silva et al, 2015), whilst other studies analyzing soccer players showed higher average scores (Da Fonseca et al, 2007;Daneshjoo et al, 2013).…”
Section: Juliete Palandi Elizze Ziero Ducatti Michele Poletti Vinícontrasting
confidence: 85%
“…In the analysis of the average PT scores of the extensor and flexor muscles at angular speed 60º/s, both limbs showed average scores higher than the average scores found in other sports such as soccer (Zakas, 2006;Fousekis et al, 2010;Eniseler et al, 2012;Daneshjoo et al, 2013), futsal (Ferreira et al, 2010), rugby (Brown et al, 2014), basketball (Schiltz et al, 2009;Carvalho et al, 2011), handball (González-Ravé et al, 2014, and volleyball (Markou & Vagenas, 2006;Shu & Zhou, 2011). However, two studies which analyzed professional soccer players showed higher average scores of flexors than the scores of the athletes of this study (Zabka et al, 2011;Daneshjoo et al, 2013). Compared to other sports at angular speed of 180°/s, a few studies have shown average scores of the extensors lower than those of this study, similarly to the studies which analyzed futsal players (Ferreira et al, 2010), and soccer (Zakas, 2006;Fousekis et al, 2010;Silva et al, 2015), whilst other studies analyzing soccer players showed higher average scores (Da Fonseca et al, 2007;Daneshjoo et al, 2013).…”
Section: Juliete Palandi Elizze Ziero Ducatti Michele Poletti Vinícontrasting
confidence: 85%
“…In this study, a pre-intervention asymmetry greater than 10% was found in flexors' PT at 60°/s and in extensors' PT at 180°/s, characterizing a risk factor for injuries 5 . In the post-intervention analysis no such asymmetries were found, suggesting that the protocol influenced the reduction of strength asymmetries between limbs.…”
Section: Discussionmentioning
confidence: 55%
“…The most used parameters in athletes' functional performance characterization are peak torque (PT), power (POW), total work (TW), fatigue index (FI) and agonist-antagonist relationship (AAR) 16,17 . Asymmetries greater than 10% in limbs' peak torque represent a high risk of injuries 5 . Normal AAR values are 60% at low speeds (60-180°/s) and 80% at high speeds (300°/s) 5 .…”
Section: Isokinetic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Força muscular é um termo amplo que se refere à habilidade do tecido contrátil de produzir tensão e uma força resultante com base nas demandas impostas sobre o músculo 2 . A força muscular é um importante componente da prestação desportiva, por essa razão a avaliação da força muscular com recurso da dinamometria isocinética é largamente utilizada 3 . Os valores de força, além de ter um componente individual e genético, são também afetados pelo sexo, idade, nível do atleta e pela modalidade esportiva praticada 4 .…”
Section: Introductionunclassified